Perceptions of English Use and Cultural Identity in Non-Native Contexts - Diva Pangestu Ispriadi; Khusnul Khatimah; Dzul Rachman (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
English plays an increasingly important role in shaping communication practices and identity negotiation in non-native contexts. This study aims to explore how English is used in daily life and how it relates to cultural identity among non-urban Indonesian university students. Employing a qualitative case study design, data were collected through semi-structured interviews with four English education students (N1–N4) from different universities in Samarinda, East Kalimantan. The data were analyzed using thematic analysis involving coding, categorization, and theme development. The findings show that English is regularly used in academic, social, and digital contexts, extending beyond formal classroom settings. Students generally expressed positive emotional attitudes toward English, describing it as enjoyable and useful, while also acknowledging challenges related to confidence and vocabulary. Importantly, English use was not perceived as threatening Indonesian cultural identity. Instead, participants demonstrated active negotiation between global communication and local cultural affiliation, viewing English as an additional communicative and identity resource rather than a replacement for local culture. This study contributes to English as a Lingua Franca and identity research by highlighting global–local identity balance in a non-urban Indonesian context, an area that remains underexplored in previous studies.